1994
DOI: 10.1002/bit.260431113
|View full text |Cite
|
Sign up to set email alerts
|

Crossflow filtration of yeast broth cultivated in molasses

Abstract: A broth of yeast cells cultivated in molasses was crossfiltered with a thin-channel module. The permeation flux gradually decreased at a constant cell concentration. The flux was much lower than that obtained for yeast broth cultivated in yeast extract, polypeptone, and dextrose (YPD) medium during the filtration. The flux did not depend on the membrane pore size (0.45 to 5 mum). The steady-state flux was one-twentieth that calculated for a cake filtration mode from the amount of cake per unit filtration area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 8 publications
5
23
0
Order By: Relevance
“…A number of investigators Kim et al, 2001;Dharmappa et al, 1992;Wickramasinghe, 1999;Huisman et . al., 1999;Tanaka et al, 1994;Chellam and Wiesner, 1998 have shown that, for polydisperse feeds, the presence of smaller particles often leads to lower permeate fluxes during microfiltration than would be expected based on the average particle size. Thus, determining the properties of the particle-size distribution after flocculation is essential in order to predict the effect of flocculation on the permeate flux.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators Kim et al, 2001;Dharmappa et al, 1992;Wickramasinghe, 1999;Huisman et . al., 1999;Tanaka et al, 1994;Chellam and Wiesner, 1998 have shown that, for polydisperse feeds, the presence of smaller particles often leads to lower permeate fluxes during microfiltration than would be expected based on the average particle size. Thus, determining the properties of the particle-size distribution after flocculation is essential in order to predict the effect of flocculation on the permeate flux.…”
Section: Introductionmentioning
confidence: 99%
“…Solid medium components may cause cake clogging [17] while concentration polarisation of soluble components may also be significant if solute rejection occurs [18]. Both of these phenomena may increase the effective specific cake resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This can have a significant effect on the critical flux, for instance the SIDM predicts a critical flux dependence on particle diameter to the power of 4/3. A number of other investigators (15,(21)(22)(23)(24)(25) have either shown or suggested that the presence of smaller particles often leads to lower permeate fluxes during microfiltration than may be expected based on the mean particle size.…”
Section: Effects Of Particle Sizementioning
confidence: 99%